Human resource management ecosystem in the context of business digitalization. - D. S. Salin; N. V. Vittenbeck (Управленческие науки)
In the context of digital economy business is increasingly choosing the ecosystem model of development, which leads to scientific interest in the formation of new approaches to human resource management (HRM). The role of human capital within business ecosystems is growing; both internal and external participants create its value to the organization. Many stakeholders get involved in working out HRM solutions, including managers, employees, HR specialists, ecosystem partners, suppliers and HR services providers. With a view of co-creating value and enhancing business competitiveness in the market, there comes a need for the formation of HRM ecosystems integrating necessary resources. The aim of the research is to determine the characteristic features and structural model of HRM ecosystems in the context of business digitalization. Currently, HRM ecosystems are at an early stage of formation and represent technocratic models in the form of a «marketplace» of multiple HR tools, which constitutes the risk of their overloading and turning into a “patchwork” of digital technologies. The emerging transition towards human-centric HRM ecosystems shifts the focus from technologies to strategic business goals and people’s well-being in the working place. The scientific result of the research is the identification of technocratic and human-centric HRM ecosystems distinctive features as well as the suggestion of a structural model-in transit, comprising humanitarian and technological components. Within the research, there were used general scientific methods of comparison, analysis, generalization, as well as scientific interpretation of the authors’ theoretical and practical experience. The research outcomes may be of interest to scientific and business communities in terms of developing the methodology of the ecosystem approach to HRM in the context of business digitalization.